Epidemiological Investigation and Virus Tracing of a Measles Outbreak in Zhoushan Islands, China, 2019 - Hui Zhang; Can Chen; An Tang; Bing Wu; Leijie Liu; Mingyu Wu; Hongling Wang (Frontiers in Public Health, 2020)
Background: Measles transmissions due to case importations challenge public health systems globally and herd immunities in all countries. In 2019, an imported measles case and its subsequently outbreak was found in the Zhoushan Islands. Here, the process of epidemiological investigation and virus tracing were summarized to provide references for the prevention and control of measles in the future.Materials and methods: The data on the demographic, epidemiological, and clinical manifestation of measles cases in this outbreak were collected. The 450 bp fragments of the measles virus (MeV) N gene were amplified and sequenced. The genome of the first imported case was further isolated. Then, the maximum-likelihood and time-scaled phylogenetic analysis was conducted.Results: A total of 28 measles cases were confirmed. Their onsets were between March 13 and May 18, 2019. The first patient was from the Ukraine. He was confirmed at the Fever Clinic in Zhoushan hospital on March 15, 2019 and at the same time, another patient had visited the hospital due to another illness and 10 days later, this second case had onset (March 25, 2019). The epidemic curve shows sustained community transmission. The majority of the following cases (19/26) were clustered on the Donggang street which was close to where the second case worked. The 22 measles virus strains successfully isolated from this outbreak all belonged to the D8.2a sub-cluster and clustered with the KY120864/MVs/GirSomnath.IND/42.16/[D8] which was the predominant genotype in the Ukraine during 2018-2019. The analysis of the complete D8 genotype genome pointed to the fact that this prevailing strain originated from India in 2015 and its substitution rate was estimated as 6.91 × 10−4 (5.64–7.98 × 10−4) nucleotide substitutions/site/year.Conclusion: This outbreak was caused by an imported case from the Ukraine. There was a possible nosocomial infection between the first case and the second case. Then, the second case played an important role in the spread of virus due to her occupation. The molecular phylogenetic analysis could help to track the origin of the virus. Increasing and maintaining the high level of vaccination coverage (≥95%) and an efficient response to imported cases are essential to prevent and control the recurrence and outbreak of measles virus.